Is It Possible to Save Russian Textile and Apparel Industry? - Regina Resheteeva (Journal of Economic Sociology, 2014)
The regular workshop “Economic Policy during the Transitional Period”, organized by professor Gregory Yasin (academic supervisor of the Higher School of Economics), was held on January 30, 2014. At this workshop professor Vadim Radaev (first vice-rector of HSE) delivered a report on “Is It Possible to Save Russian Apparel and Textile Industry?”, initiating a discussion of the current problems faced by the industry and development perspectives. Prominent experts in this sphere took part in debates on the future of Russian apparel and textile industry: Vugar Isaev (president and founder of the chain stores “Snezhnaya Koroleva”), Andrei Razbrodin (president of The Russian Union of Entrepreneurs of Textile and Light Industry, board member of TheRussian Union of Industrialists and Entrepreneurs), Andrei Yakovlev (director of the Institute for Industrial and Market Studies).The central issue discussed at the workshop dealt with the reasons of the Russian textile and apparel industry survival after Soviet Union collapse despite sharp productivity decline. Nevertheless textile and apparel industry still vulnerable, facing the risks posed by global competition. Vadim Radaev suggests modernization strategies for textile and apparel, facilitating its growth. Do we have chances to enter in global supply chains? What role should government and companies play in this process? This article provides an overview of answers to those questions.